Northern Catandunganon Men and Women Speakers in Focus: Investigating Angry Registers - Richard Sambajon Agbayani; Jimmylen Zuǹiga Tonio (Randwick International of Education and Linguistics Science Journal, 2023)
Angry Registers (ARs) are evident in situations where they are used, such as when someone is angry. This study endeavored to examine the characteristics and functions of angry registers in the discourse of 90 participants (45 men and 45 women) from four municipalities of Northern Catanduanes region in Bicol, Philippines. The data collection was ensured through the use of observation sheets and follow-up interviews. The investigation is grounded on the perspectives of Speech Register Theory, and is quantitative-qualitative in nature. Findings revealed that there are 26 angry registers used; 14 from male and 19 from female speakers. These ARs are classified as nouns, verbs, and adjectives. Noun ARs are related to body parts, person, animals, and inanimate objects. Verb ARs prompt an action or movement or imply a threat. Adjectival ARs are all words that negatively describe a person usually associated to female attributes. Participants also are not merely user of one AR in their utterance as instances of two ARs combined are applied. Further, results specified that the primary functions of speaking ARs across genders are the desire to release the feelings of anger and frustrations, to emphasize emotional reactions to others and to express intense emotion without offending others. Generally, women are more likely than men in using these angry registers in discourse.